Geographical disparities in the prognosis of patients with nasopharyngeal carcinoma treated with intensity-modulated radiation therapy: a large institution-based cohort study from an endemic area. Issue 11 (10th November 2020) - Lin, Si-Ting; Meng, Dong-Fang; Yang, Qi; Wang, Wei; Peng, Li-Xia; Zheng, Li-Sheng; Qiang, Yuan-Yuan; Mei, Yan; Xu, Liang; Li, Chang-Zhi; Peng, Xing-Si; Hu, Hao; et al.
Abstract : Objectives: Geographical disparities have been identified as a specific barrier to cancer screening and a cause of worse outcomes for patients with cancer. In the present study, our aim was to assess the influence of geographical disparities on the survival outcomes of patients with nasopharyngeal carcinoma (NPC) treated with intensity-modulated radiation therapy (IMRT). Design: Cohort study. Setting: Guangzhou, China. Participants: A total of 1002 adult patients with NPC (724 males and 278 females) who were classified by area of residence (rural or urban) received IMRT from 1 January 2010 to 31 December 2014, at Sun Yat-sen University Cancer Center. Following propensity score matching (PSM), 812 patients remained in the analysis. Main outcome measures: We used PSM to reduce the bias of variables associated with treatment effects and outcome prediction. Survival outcomes were estimated using the Kaplan-Meier method and compared by the log-rank test. Multivariate Cox regression was used to identify independent prognostic factors. Results: In the matched cohort, 812 patients remained in the analysis. Kaplan-Meier survival analysis revealed that the rural group was significantly associated with worse overall survival (OS, p<0.001), disease-free survival (DFS, p<0.001), locoregional relapse-free survival (LRRFS, p=0.003) and distant metastasis-free survival (DMFS, p<0.001). Multivariate Cox regression showed worse OS (HR=3.126; 95% CI 1.902 to 5.138; p<0.001), DFS (HR=2.579; 95% CI 1.815 to 3.665; p<0.001), LRRFS (HR=2.742; 95% CI 1.359 to 5.533; p=0.005) and DMFS (HR=2.461; 95% CI 1.574 to 3.850; p<0.001) for patients residing in rural areas. Conclusions: The survival outcomes of patients with NPC who received the same standardised treatment were significantly better in urban regions than in rural regions. By analysing the geographic disparities in outcomes for NPC, we can guide the formulation of healthcare policies.